Muḥammad Asad, ek Yūrapiyan badvī: (savāniḥ ḥayāt, taṣnīfāt, mut̤ālaʿāt aur tabṣire) - Asad, Muhammad; Čaġatāʾī, Muḥammad Ikrām (Pākistān Rāʾiṭarz Koāpreṭiv Sosāʾiṭī, 2009)
Contributed articles on the life and works of Muhammad Asad, 1900 - 1992, visionary Islamic scholar from Poland; also includes some of his own writings